Gugatan Ganti Rugi Waduk Bendo Desa Ngindeng Kecamatan Sawoo Kabupaten Ponorogo - Tanzilullah, Muhammad Ilham; Sari, Maya Puspita; Amirudin, Ahmad; Abdullah, Boy Mustaqim (El-Dusturie, 2023)
Infrastructure developments, such as the Bendo Reservoir in Ponorogo Regency, often have significant socio-economic impacts on affected communities. This study aims to reveal the impact of the construction of the Bendo Reservoir in Ngindeng Village, Sawoo District, Ponorogo Regency, particularly regarding the relocation of residential areas, loss of agricultural land, and environmental changes. This study used a qualitative approach involving in-depth interviews with various stakeholders, including residents of Ngindeng Village, local government representatives and related institutions. In addition, data was also collected through document studies, including information on the construction of the dam, government policies regarding compensation, and socio-economic data of the local community before and after the construction of the dam. The results of the study revealed that the people of Ngindeng Village experienced complex consequences as a result of the construction of the Bendo Reservoir. The forced displacement of residents from their homes causes social and economic instability. Loss of agricultural land also affects the people's main livelihood, while environmental changes have an impact on the sustainability of natural resources. Even though the government has provided compensation and compensation, the results of the study found that there were still dissatisfaction and feelings of injustice among the residents regarding the amount and quality of the compensation given. In handling compensation claims, this study also explores the settlement process through legal mechanisms and mediation efforts, as well as identifying the obstacles encountered. This research has important implications for policy makers in the process of planning and implementing infrastructure projects. These findings highlight the need for a more inclusive and participatory approach in involving affected communities in development decision-making. In addition, more attention is needed on handling compensation claims in a fair and transparent manner in order to reach a sustainable agreement between the parties involved.Pembangunan infrastruktur, seperti Waduk Bendo di Kabupaten Ponorogo, seringkali menimbulkan dampak sosial-ekonomi yang signifikan bagi masyarakat terdampak. Penelitian ini bertujuan untuk mengungkap dampak dari pembangunan Waduk Bendo di Desa Ngindeng, Kecamatan Sawoo, Kabupaten Ponorogo, khususnya terkait relokasi pemukiman warga, kehilangan lahan pertanian, dan perubahan lingkungan. Penelitian ini menggunakan pendekatan kualitatif dengan melibatkan wawancara mendalam dengan berbagai pihak terkait, termasuk warga Desa Ngindeng, perwakilan pemerintah daerah, dan lembaga terkait. Selain itu, data juga dikumpulkan melalui studi dokumen, termasuk informasi tentang pembangunan waduk, kebijakan pemerintah mengenai ganti rugi, dan data sosial-ekonomi masyarakat setempat sebelum dan setelah pembangunan waduk. Hasil penelitian mengungkapkan bahwa masyarakat Desa Ngindeng mengalami konsekuensi yang kompleks akibat pembangunan Waduk Bendo. Pemindahan paksa warga dari tempat tinggal mereka menyebabkan ketidakstabilan sosial dan ekonomi. Kehilangan lahan pertanian juga mempengaruhi mata pencaharian utama warga, sementara perubahan lingkungan berdampak pada keberlanjutan sumber daya alam. Meskipun pemerintah telah memberikan kompensasi dan ganti rugi, hasil penelitian menemukan bahwa masih terdapat ketidakpuasan dan perasaan tidak adil di kalangan warga terkait jumlah dan kualitas ganti rugi yang diberikan. Dalam penanganan gugatan ganti rugi, penelitian ini juga mengeksplorasi proses penyelesaian melalui mekanisme hukum dan upaya mediasi, serta mengidentifikasi kendala-kendala yang dihadapi. Penelitian ini memiliki implikasi penting bagi pengambil kebijakan dalam proses perencanaan dan implementasi proyek infrastruktur. Temuan ini menyoroti perlunya pendekatan yang lebih inklusif dan partisipatif dalam melibatkan masyarakat terdampak dalam pengambilan keputusan pembangunan. Selain itu, diperlukan perhatian lebih pada penanganan gugatan ganti rugi secara adil dan transparan untuk mencapai kesepakatan yang berkelanjutan antara pihak-pihak yang terlibat.